Adaptive wavelet estimations for the derivative of a density in GARCH-type model - Kaikai Cao; Jingyi Wei (Journal of Inequalities and Applications, 2019)
Abstract Recently, Rao investigated the estimations for the derivative of a density in GARCH-type model S=σ2Z $S=σ ^{2}Z$ over L2 $L^{2}$-risk (Commun. Stat., Theory Methods 46:2396–2410, 2017). This paper extends those estimations to Lp $L^{p}$-risk ( 1≤p<∞ $1≤ p<∞ $). In addition, we provide a lower bound for this model, which indicates one of our convergence rates to be nearly-optimal.